Co-production of bio-oil and propylene through the hydrothermal liquefaction of polyhydroxybutyrate producing cyanobacteria. (May 2016) - Wagner, Jonathan; Bransgrove, Rachel; Beacham, Tracey A.; Allen, Michael J.; Meixner, Katharina; Drosg, Bernhard; Ting, Valeska P.; Chuck, Christopher J.
Highlights: PHB breaks down into propylene and carbon dioxide under HTL conditions. The product distribution is not effected by other biomolecules present. PHB containing cyanobacteria (7.5%) yielded 2.6% propylene. Propylene could be co-produced with low-N bio-oils in a potential biorefinery. Abstract: A polyhydroxybutyrate (PHB) producing cyanobacteria was converted through hydrothermal liquefaction (HTL) into propylene and a bio-oil suitable for advanced biofuel production. HTL of model compounds demonstrated that in contrast to proteins and carbohydrates, no synergistic effects were detected when converting PHB in the presence of algae. Subsequently, Synechocystis cf. salina, which had accumulated 7.5 wt% PHB was converted via HTL (15% dry weight loading, 340 °C). The reaction gave an overall propylene yield of 2.6%, higher than that obtained from the model compounds, in addition to a bio-oil with a low nitrogen content of 4.6%. No propylene was recovered from the alternative non-PHB producing cyanobacterial strains screened, suggesting that PHB is the source of propylene. PHB producing microorganisms could therefore be used as a feedstock for a biorefinery to produce polypropylene and advanced biofuels, with the level of propylene being proportional to the accumulated amount of PHB.